Tugas Dan Fungsi Dewan Keamanan PBB Dalam Penyelesaian Sengketa Internasional (Secara Damai) - Khaidir Anwar (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The Security Council is one of equipment of the United Nations whose functions and assignments are to maintain the harmony, security, and piece of the world. The security council of the United Nations in conducting its functions and assignments occasionally determines the resolution. However, many are questioning the supporting force of the resolution. In this study, the assignments and functions of the security council of the United Nations as well as the supporting force of the resolution determined are discussed.